The Dominant Personality Type in Hemiparetic Patients - Andika Darmawan Wahono; Abdurachman Abdurachman; Khairina Khairina; Sita Setyowatie (Health Notions, 2022)
McCrae and Costa proposed the big five personality which includes neuroticism, extraversion, openness, agreeableness, and conscientiousness. Certain personalities appear to be dominant in terms of the relevant disease. The aim of this study was to investigate the dominant personality according to the Big Five personality in hemiparetic patients. A descriptive cross-sectional with a survey-based questionnaire design involving 72 hemiparetic patient from outpatient department of Neurology Dr.Soetomo General Hospital hemiparesis in January 2020 to June 2021 was employed. The big five questionnaire was administered online or sent by courier. There were 27 female and 45 male in total with mean age of 53.89 years (SD 12.53). Majority of the hemiparese patiets had a agreeableness dominant personality (N=55). In addition, it was found that 1 hemiparese patient had an openess dominant personality, 3 hemiparese patients had a conscientious dominant personality, 6 hemiparese patients had an extraversion dominant personality, 4 hemiparese patients had a neuroticism dominant personality, and the remaining 3 had a mixed dominant personality. The dominant personality type in hemiparesis patient is agreeableness.Keywords: dominant; hemiparese; personality